Peptoid‐Loaded Microgels Self‐Defensively Inhibit Staphylococcal Colonization of Titanium in a Model of Operating‐Room Contamination. Issue 31 (13th September 2022) - Zhao, Wenhan; Wang, Haoyu; Xiao, Xixi; De Stefano, Lauren; Katz, Jordan; Lin, Jennifer S.; Barron, Annelise E.; Schaer, Thomas P.; Wang, Hongjun; Libera, Matthew
Abstract: Bacterial contamination of an exposed implantable medical device by the atmosphere of an operating room (OR) is increasingly implicated as a cause of device‐associated infection. Here, OR contamination is modeled in vitro using an aerosolizing system to spray small quantities of staphylococci onto titanium rods. Contaminated rods always manifest culturable bacteria. Self‐assembly is used to create a self‐defensive Ti surface that substantially enhances the rod's resistance to such contamination. Poly(acrylic acid) microgels are electrostatically deposited onto small Ti rods and subsequently loaded by complexation with a cationic antimicrobial peptoid (TM1). The microgels are visualized in situ by optical microscopy, and changes in microgel diameter indicate the loading state. These measurements show that TM1 can be quickly loaded from low‐ionic‐strength buffer and subsequently remained sequestered within the microgels for up to 4 weeks when soaked in phosphate buffered saline. TM1‐loaded microgel‐modified Ti surfaces are contaminated with aerosolized staphylococci, and subsequent assays indicate few or no culturable bacteria. In the absence of nutrients to enable metabolism, this finding suggests that bacteria trigger local TM1 release by contact transfer. The modified surfaces exhibit good in vitro cytocompatibility as manifested by the adhesion, spreading, and metabolic activity of human fetal osteoblasts. Abstract : An in vitro model of operating‐room contamination shows that the staphylococcal colonization of a titanium rod is prevented by modifying the Ti surface with a sub‐monolayer of poly(acrylic acid) microgels loaded by complexation with a cationic antimicrobial peptoid (TM1). Self‐defensive bacteria‐triggered peptoid release occurs by contact transfer. The modified surface remains cytocompatable, and osteoblasts do not trigger TM1 release.